Pengembangan Sistem Informasi Manajemen Supplier dan Barang dengan Extreme Programming - Astria Hijriani; Jannati Asri Safitri; Raden Irwan Adi Pribadi; Rico Andrian (Maranatha University Press, 2020)
The case study was taken from one of trading companies in Lampung. The company sells Muslim fashion products from a large number of suppliers. Suppliers data is recorded in detail manually, as well as products recorded. Manual data collection can result in recording errors, data easily tucked, or not recorded. This research develops an information system to help the company in data collection of suppliers and products automatically based on web using Laravel as a framework. This system is built using extreme programming methods and has features that focus on collecting suppliers, products, and product shipments. The results of system testing using the black box testing method shows that the system has fulfilled functional requirements and user needs. Keywords— Management Information System; Product; Supplier.